Causa Gratiae – Theological Analysis of Augustine’s on Grace and Free Will - Tomas Gulan (Communications - Scientific letters of the University of Zilina, 2007)
Augustine is unanimously considered to be the greatest church father of western Christianity. His major theological controversy was against Pelagianism, a Christian heresy identifying God’s grace with His endowment of man with free choice in creation. When challenged to address the issue of juxtaposition of God’s grace and human free choice, Augustine responds by writing On Grace and Free Will, where he opens his discussion by the proof of free choice. Further in the argument, however, he definitely abandons this notion and moves towards lifting up and praising the primacy and sole agency of the activity of God’s grace.